As a downstream target of the AKT pathway, NPTX1 inhibits proliferation and promotes apoptosis in hepatocellular carcinoma - Zhao, Yue (Biosci Rep, 2019)
Hepatocellular carcinoma (HCC) is correlated with a poor prognosis and high mortality worldwide. Neuronal pentraxin 1 (NPTX1) has been reported to play an oncogenic role in several types of tumors. However, its expression and function in HCC is not yet fully understood. In the present study, we aimed to investigate the clinicopathological significance of NPTX1 in HCC and the underlying mechanisms. We observed that the expression of NPTX1 was decreased significantly in HCC and was associated with tumor size and metastasis in patients. Gain-of-function approaches revealed that NPTX1 suppressed the growth ability of HCC cells and contributed to mitochondria- related apoptosis. Furthermore, mechanistic investigations showed that the AKT (AKT serine/threonine kinase) pathway can regulate the effects of NPTX1 in HCC cells. After blocking the AKT pathway, the action of NPTX1 was greatly increased. In summary, we demonstrated that NPTX1 inhibited growth and promoted apoptosis in HCC via an AKT-mediated signaling mechanism. These findings indicate that NPTX1 is a potential clinical therapeutic target.